Review on critical factors of adopting cloud mobile learning - Al-Arabiat, D. (Institute of Electrical and Electronics Engineers Inc., 2015)
Cloud computing is a new technology that allows users to share computing resources (e.g., storages, software and platforms) in anytime from anywhere. This advantage can be very beneficial to be integrated with mobile devices especially for educational institutions. Cloud Mobile Learning (CML) is a new concept that has a great promise for carrying out collaborative educational activities. Decision of adopting CML remains a challenge that need to be addressed. However, this study aims to explore the factors affecting the decision to adopt CML in Higher Educational Institutions (HEIs). A systematic literature review approach used in this study to explore the main factors affecting users' satisfaction and intention to use of the new technology. The results indicated that there are an important set of factors should be considered when adopting CML new technology; such as accessibility, usefulness and privacy. Â© 2015 IEEE.